Enhancing the formability of flame-retardant magnesium alloy through Zn alloying - Xizao Wang; Ce Zheng; Tianjiao Luo; Tianyu Liu; Qiuyan Huang; Yingju Li; Yuansheng Yang (Journal of Magnesium and Alloys)
Poor formability is a key problem that limits the application of flame-retardant Mg-Al-Ca based alloys at room temperature. In this study, we present a new Mg-6Al-3Ca-0.4Mn-2Zn (wt%) alloy which exhibits excellent flame-retardant performance and excellent formability. Due to the high Ca content, the Mg-6Al-3Ca-0.4Mn-2Zn (wt%) alloy does not burn at 1065 °C. The formability of the alloys is measured using a three-point bending test, and the Mg-6Al-3Ca-0.4Mn-2Zn (wt%) alloy shows excellent formability, with a significant increase in bending displacement from 7.1 mm to 23.8 mm compared to the Mg-6Al-3Ca-0.4Mn (wt%) alloy. The combined effect of the weakened basal texture, the reduction of twins and the plastically deformable Al2Ca phase particles ensures good formability of the Mg-6Al-3Ca-0.4Mn-2Zn (wt%) alloy. The dynamic recrystallization mechanisms of the alloys have been analyzed, and the promotion of dynamic recrystallization by the PSN mechanism is responsible for the weakened basal texture and the reduction of twins in the Mg-6Al-3Ca-0.4Mn-2Zn (wt%) alloy. The new Mg alloy is attractive for industrial applications due to its excellent flame-retardant performance and formability.